ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP PELAYANAN AKADEMIK DI STIKES SENIOR MEDAN - Dame Meldaria Sipahutar (MES: Journal of Mathematics Education and Science, 2022)
This study was conducted to determine the level of student satisfaction with academic services at STIKes Senior Medan. This research is a descriptive study that uses six variables, namely Tangible, Reliability, Responsiveness, Empathy, Assurance and Information Systems to measure the level of student satisfaction. Questionnaires in the form of a Likert scale were distributed to students through the Google Form application. Furthermore, validity and reliability tests were carried out using the Statistical Product and Service Solution (SPSS) application program to determine whether the variables used in this study were valid and reliable. By using descriptive analysis, the results obtained from the level of student satisfaction with the quality of academic services.